A novel rotary magnetorheological flexible joint with variable stiffness and damping. (21st September 2018) - Dong, Xiaomin; Liu, Weiqi; An, Guopeng; Zhou, Yaqin; Yu, Jianqiang; Lin, Qing
Abstract: To transfer torque while reducing vibration and shock, a rotary magnetorheological flexible joint (MRFJ) with tunable stiffness and damping characteristics is proposed in this study. Equivalent variable stiffness and damping principle for the MRFJ is derived analytically. The structure and parameters of the MRFJ are designed. The variable stiffness and damping characteristics of a prototype of MRFJ is measured. The test results show that the variable stiffness and damping characteristics of the MRF can be tuned independently with variable input current. The theoretic results agree well with the experimental results.